Occupational Therapy in the Philippines from founding years to the present - Bondoc, Salvador
This article documents the history of the occupational therapy profession in the Philippines from its founding years to present. The author used a historical methodology to collect primary and secondary sources of historical data; critically analyze them for genuineness; and present historical information in the most accurate and fairest possible treatment. This article highlights the occupational therapy profession?s development in the Philippines from its early beginnings in post World War II to present. Challenges facing the development and autonomy of occupational therapy as a profession in the Philippines, from the past to present are discussed. To address these challenges, this article concludes with a call for scholarship and self-advocacy in the occupational therapy profession.
Keywords: Historical inquiry; Advocacy; Professional development; Brain drain